A Review of Perfluoroalkyl Acids (PFAAs) in terms of Sources, Applications, Human Exposure, Dietary Intake, Toxicity, Legal Regulation, and Methods of Determination - Katarzyna Sznajder-Katarzyńska; Magdalena Surma; Iwona Cieślik (Journal of Chemistry)
Per- and polyfluoroalkyl substances (PFASs) are widely distributed across the world and are expected to be of concern to human health and the environment. The review focuses on perfluoroalkyl acids (PFAAs) and, in particular, on the most frequently discussed perfluoroalkyl carboxylic acids (PFCAs) and perfluoroalkane sulfonic acids (PFSAs). In this study, some basic information concerning PFASs is reviewed, focusing mainly on PFAAs (perfluoroalkyl acids). We have made efforts to systemize their division into groups according to chemical structure, describe their basic physicochemical properties, characterize production technologies, and determine potential human exposure routes with particular reference to oral exposure. A variety of possible toxicological effects to human health are also discussed. In response to increasing public concern about the toxicity of PFAAs, an evaluation of dietary intake has been undertaken for two of the most commonly known PFAAs: perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS). As summarized in this study, PFAAs levels need further assessment due to the science-based TWI standards laid down by the EFSA’s CONTAM Panel regarding the risk to human health posed by the presence of perfluorooctane sulfonic acid and perfluorooctanoic acid in food (tolerable weekly intakes of PFOA and PFOS set up to 6 ng·kg−1·bw·week−1 and 13 ng·kg−1·bw·week−1, respectively). Current legislation, relevant legislation on PFAAs levels in food, and the most popular methods of analysis in food matrices are described.